Age, growth and reproduction in creole perch (Percichthys trucha) in the Negro River, Argentinean Patagonia - Lopez Cazorla, Andrea Cecilia (2011)
Age, growth and reproductive characteristics of creole perch, Percichthys trucha, were investigated in the Negro River, southern Argentina from samples collected seasonally, December 1994-December 1995. Age was estimated via scale and whole otolith reading methods. Total length (n=413) ranged from 103 to 432mm, and weight from 12 to 1042g. Significant differences between the length-weight relationships of males and females were detected (P<0.05). Isometric growth was observed in juveniles and males, whereas total population and females exhibited positive allometric growth. The marking pattern in scales and otoliths followed an annual rhythm, with the formation of only one annulus in scales and only one hyaline band in otoliths during autumn-winter. The oldest males were 5years old whereas maximum age in females was 12years from scales and 15years from otoliths. Because scales were found to underestimate age in individuals older than 4years, otoliths were considered to be the best structures for creole perch age determination. Gompertz growth parameters based on otolith data were L∞: 428.0mm, k=0.46 and t0=0.43 for total population (r=0.90), L∞: 410.7mm, k= 0.42 and t0=0.46 for males (r=0.91), and L∞: 434.1mm, and k=0.49 and t0=0.43 for females (r=0.91). Lengths at first maturity (TL50) were 260 and 241mm in males and females, respectively, both of which corresponded to ages between 1 and 2years. Macroscopic gonad inspection and the high percentage of juveniles captured during summer indicated that spawning begins at the end of spring. © 2010 Blackwell Verlag, Berlin.